(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Social media is a subject of government interest in emergency response. Government usage of social media in crisis has four functions: information display, information obtain, public expression platform and interaction tool. Though much attention has been given on government usage of social media in crisis, little research is focused on governments interaction with public via social media. This research did a case study on how government agencies of New York City (NYC) use social media to frame crisis and interact with public. By coding crisis framing and counting public re-tweets per tweet, public question, government reply and public positive and negative attitude numbers of five main crisis management agencies in NYC. The findings indicate that public and government had different attentions over crisis; NYC government had a relative high interaction intensity with public and interaction with public may influence public attitude. This research concludes some advice for government using social media in crisis.